Happiness and Positivity at Workplace in Context of Spirituality: A Conceptual Framework - Dhamija, Aruna (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Happiness when associate with spirituality in the workplace may be one of the hardest tasks for the employees who have ever witnessed. The potential threat to manage work with happiness in every profession due to competition, expectations and new challenges has engulfed the organizations by now. Employees react differently in their style that depends on how much the individual is spiritual and reflecting happiness at the workplace. This paper attempts to determine the ways to remain happy at the workplace with the help of the Alexander Krolof model. The purpose of this study is to manage the difficult situation and bolster efficiency and effectiveness at the workplace.